Adaptive smartphone-based sensor fusion for estimating competitive rowing kinematic metrics - Cloud, B.; Tarien, B.; Moore, J. (2018)
Competitive rowing highly values boat position and velocity data for real-time feedback during training, racing and post-training analysis. The ubiquity of smartphones with embedded position (GPS) and motion (accelerometer) sensors motivates their possible use in these tasks. In this paper, we investigate the use of two real-time digital filters to achieve highly accurate but reasonably priced measures of boat speed and distance traveled. Both filters combine acceleration and location data to estimate boat distance and speed; the first using a complementary frequency response-based filter technique, the second with a Kalman filter formalism that includes adaptive, real-time estimates of effective accelerometer bias. The estimates of distance and speed from both filters were validated and compared with accurate reference data from a 10 Hz differential GPS system with better than 1 cm precision, in experiments using two subjects (an experienced club-level rower and an elite rower) in two different boats on a 300 m course. Relative to single channel (smartphone GPS only) measures of distance and speed, the complementary filter improved the accuracy and precision of boat speed, boat distance traveled, and distance per stroke by 44%, 42%, and 73%, respectively, while the Kalman filter improved the accuracy and precision of boat speed and distance per stroke by 51% and 72%, respectively. Both filters demonstrate promise as general purpose methods to substantially improve estimates of important rowing performance metrics.